Restoring Lantana camara Invaded Tropical Deciduous Forest: The Response of Native Plant Regeneration to two Common Lantana Removal Practices - Hiremath, Ankila J.; Prasad, Ayesha; Sundaram, Bharath (Indian Forester, 2018)
Lantana camara (hereafter, Lantana), a pantropical invasive species, has become widespread across India. Lantana forms dense thickets in the understory of deciduous forests, adversely affecting regeneration of native vegetation and habitat for wildlife. Lantana removal is now an integral part of protected area management in India. We tested the relative efficacy of two Lantana removal techniquesâ€”cutting and burning, and uprootingâ€”commonly employed by forest managers. Our objectives were a) to see which technique resulted in better native plant recovery post- Lantana removal; and b) to evaluate the mechanisms underpinning Lantana’s success in these forests. The two techniques did not differ greatly in post-removal recovery of native vegetation. However, there was a marked difference in the post-removal recovery of Lantana. Lantana in the uprooted plots was significantly denser than in the cut-and-burnt plots, making the latter the more effective of the removal techniques. Given the numerical dominance of Lantana seeds in the soil, and their wide dispersal, no Lantana removal is likely to be effective without post-removal monitoring and weeding. We also recommend post-removal planting of species that can pre-empt Lantana re-colonization, and respond positively to disturbances like fire and grazing, that are known to promote Lantana’s spread.